2003
DOI: 10.1200/jco.2003.07.010
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Number of Lymph Nodes Sampled on Outcome in Patients With Stage I Non–Small-Cell Lung Cancer

Abstract: These results indicate that examining a greater number of lymph nodes in patients with stage I NSCLC treated with resection increases the likelihood of proper staging and affects patient outcome. Such information is important not only for therapy and prognosis of individuals but also for identifying those who may benefit from adjuvant therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
181
2
2

Year Published

2004
2004
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 261 publications
(196 citation statements)
references
References 17 publications
10
181
2
2
Order By: Relevance
“…For the removal of mediastinal lymph nodes, many investigators insist on the importance of systematic nodal dissection (SND) for accurate staging (4)(5)(6)(7)(8)(9)(10).…”
Section: Effect Of Mediastinal Lymph Nodes Sampling In Patients With mentioning
confidence: 99%
“…For the removal of mediastinal lymph nodes, many investigators insist on the importance of systematic nodal dissection (SND) for accurate staging (4)(5)(6)(7)(8)(9)(10).…”
Section: Effect Of Mediastinal Lymph Nodes Sampling In Patients With mentioning
confidence: 99%
“…Among all the lung cancer-therapeutic methods, surgery plays a pivotal role, especially in the early-stage nonsmall cell lung cancer (NSCLC). Nowadays, the standard surgical treatment of early-stage NSCLC is lobectomy with systematic lymph node dissection (LND) as recommended by the guidelines (3,4), which capable of providing accurate staging (5,6), detecting occult metastasis (7) and improving survival (5,8,9). However, randomized trials have not demonstrated that LND has more survival benefit than sampling (7,10).…”
Section: Introductionmentioning
confidence: 99%
“…This figure seems to be superior to the absolute number of metastatic lymph nodes in predicting the prognosis and to be useful in reducing stage migration in types of solid cancers such as cancers of the stomach [8][9][10], breast [11], bladder [12], pancreas [13], and lung [14].…”
Section: Introductionmentioning
confidence: 99%